2021
DOI: 10.1002/kin.21486
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐phase OH oxidation kinetics of pyrazine, pyrimidine, and pyridazine

Abstract: The gas-phase kinetics of the OH-oxidation of three six-membered nitrogen heterocycles C 4 N 2 H 4 isomers, namely pyrazine, pyrimidine, and pyridazine, were determined in a photochemical reactor coupled to a FTIR spectrometer and a SPME-GC/MS, at atmospheric pressure over the temperature range 298-353 K. Experiments were conducted using the relative rate method where two different references were employed for each studied compound. The obtained Arrhenius expressions are (in cm 3 molecule -1 s -1 ) OH+pyrazine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…It is also found that hydrogen abstraction channels always dominate. The obtained rate constants are close to the experimental ones obtained by Samir et al 4 and full agreement can be obtained by adjustments of the barrier heights by less than 1 kcal mol -1 .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…It is also found that hydrogen abstraction channels always dominate. The obtained rate constants are close to the experimental ones obtained by Samir et al 4 and full agreement can be obtained by adjustments of the barrier heights by less than 1 kcal mol -1 .…”
Section: Discussionsupporting
confidence: 88%
“…5 Field measurements to assess the atmospheric concentration of diazine isomers are lacking, but there is information related to the persistence of pyrimidine and its derivatives. 6 The recent experimental research done by Samir et al 4 employed a rigid atmospheric simulation chamber coupled to an FTIR spectrometer and SPME-GC/MS over the temperature range 298-353 K at atmospheric pressure, providing rate constants for OH oxidation of the diazine isomers, which are as follows in cm 3 molecule -1 s -1 at 298 K: 𝑘 𝑃𝑦𝑟𝑎𝑧𝑖𝑛𝑒 = 4.11 × 10 −13 , 𝑘 𝑃𝑦𝑟𝑎𝑑𝑖𝑧𝑖𝑛𝑒 = 3.12 × 10 −13 , 𝑘 𝑃𝑦𝑟𝑎𝑚𝑖𝑑𝑖𝑛𝑒 = 3.48 × 10 −13 . Accordingly, tropospheric lifetimes of 29, 37, and 34 days were found for pyrazine, pyridazine, and pyrimidine, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations